Analysis Of The Quality Improvement Management Process Through PDSA At Puskesmas Sidoarjo Sidoarjo District - Retikasari, Frysca Virnanda; Ghani, Danang Abd; Maghfiroh, Apriliana Lailatul; Finishia, Firmanni (Medical Technology and Public Health Journal, 2025)
Improving the quality of health center is very important to realize quality and equitable health services. This study aims to analyze the implementation of continuous quality management through the PDSA (Plan-Do-Study-Action) cycle at Sidoarjo Health Center. The method used is descriptive comparative to compare Deming’s PDSA theory with its implementation based on the Sidoarjo Health Center Quality Improvement Report Year 2024. The results showed that there were shortcomings in the preparation of details at the Plan step, such as the non-use of root cause analysis tools (fishbone or 5 whys), and the absence of success criteria. At the Do and Study steps, assessment of plan implementation and evaluation of plan effectiveness was not optimal. The Action step has also not been implemented in detail, and the follow-up plan has not described the evaluation results of the Study.